Strengthening urban community resilience through fire risk education and mitigation in Depok City - Suparni, Suparni; Utari, Dyah; Jannah, Farahul; Amraeni, Yunita; Aliyyah, Nurusysyarifah (Universitas Muhammadiyah Magelang, 2025)
Fire is a primary non-natural disaster threat in densely populated urban areas like Depok City. This community service program aims to enhance community capacity in Limo District through fire risk mitigation and household prevention techniques. The implementation method involved focus group discussions with community leaders and participatory education utilizing presentations, posters, and flyers. Community knowledge was measured through pre-test and post-test questionnaires. The results demonstrated a significant increase in fire safety literacy, with knowledge scores rising from 78.11% to 89.19%. The program's success was driven by active citizen participation and strong support from village officials and local leaders. These findings emphasize that multi-stakeholder collaboration and communicative visual education approaches are crucial prerequisites for building community self-reliance in fire disaster mitigation within urban environments.